2021
DOI: 10.1002/ejic.202100202
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate‐Based Metal‐Organic Framework/Polypyrrole Composites toward Enhanced Supercapacitor Performance

Abstract: Supercapacitors are energy storage equipment that have attracted particular attention owing to its wide operating temperature range, high-power density, and small size, whereas the limited energy density has always been a main obstacle in many applications. Composite materials have a forward-looking application value in the manufacture of innovative supercapacitors due to the synergistic effect between various components. We propose a plain oxidative polymerization method to prepare the polyoxometalate-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Figure 7f provides the Ragone plot, illustrating the calculated relationship between the energy and power densities of the fabricated SSCD by employing Equations ( 2) and (3). Remarkably, the MF(ht) SSC device attains an impressive peak energy density of 74.7 Wh/kg at a power density of 3780 W/kg, surpassing previously reported values for both energy and power densities [6,[48][49][50]. For an extensive comparative analysis of these parameters with those of other symmetric supercapacitor devices, please refer to Table 2.…”
Section: Supercapacitor Two-electrode Device Performance Evaluationmentioning
confidence: 74%
“…Figure 7f provides the Ragone plot, illustrating the calculated relationship between the energy and power densities of the fabricated SSCD by employing Equations ( 2) and (3). Remarkably, the MF(ht) SSC device attains an impressive peak energy density of 74.7 Wh/kg at a power density of 3780 W/kg, surpassing previously reported values for both energy and power densities [6,[48][49][50]. For an extensive comparative analysis of these parameters with those of other symmetric supercapacitor devices, please refer to Table 2.…”
Section: Supercapacitor Two-electrode Device Performance Evaluationmentioning
confidence: 74%
“…A Keggin-type polyoxometalate (PMo 12 ) was first reported to be used as the anode material of LIBs in 2012, and it was found that each PMo 12 molecule reversibly transfers 24 electrons during the lithiation and delithiation processes . From then on, some smaller POMs, including PMo 12 , PMo 10 V 2 , PW 12 , , SiW 12 , Co 8 W 12 , and so on, which are combined with functional support materials, such as MXene, organic linkers, , MOFs, CNTs, , and GO, , were mainly reported for energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Many composite and nanocomposite materials are currently being developed using PPy. For example, Li et al [ 4 ] prepared polyoxometalate-based metal-organic framework/PPy composites by oxidative polymerization method to be used as electrodes in supercapacitors. It has been reported that the obtained composite electrodes contain abundant active regions with suitable pores and have good conductivity.…”
Section: Introductionmentioning
confidence: 99%